Cystic fibrosis transmembrane regulator (CFTR) ΔF508 mutation and 5T allele in patients with chronic pancreatitis and exocrine pancreatic cancer. Issue 1 (1st January 2001) - Malats, N; Casals, T; Porta, M; Guarner, L; Estivill, X; Real, F X
Abstract : BACKGROUND: An increased risk of chronic pancreatitis has been described among carriers of the cystic fibrosis transmembrane regulator ( CFTR ) mutation. In addition, patients with cystic fibrosis may have a higher risk of exocrine pancreatic cancer. AIMS: To determine the prevalence of the ΔF508 mutation and 5T allele, the most common CFTR disease related variants, and to assess their association with lifestyle factors in an unselected series of patients with chronic pancreatitis or pancreatic cancer. SUBJECTS: Patients recruited to the multicentre PANKRAS II study with a diagnosis of chronic pancreatitis and pancreatic cancer from whom normal DNA was available. METHODS: The ΔF508 mutation and 5T allele were analysed using polymerase chain reaction amplified normal DNA. Information on clinical and lifestyle factors was obtained through personal interviews. RESULTS: Among patients with pancreatitis, no ΔF508 alleles were found and the prevalence of the 5T allele was 10.5%, similar to that described in the general population. Among patients with pancreatic cancer, the prevalence of the ΔF508 mutation and the 5T allele was 2.4% and 5.5%, respectively. 5T allele carriers with cancer consumed significantly less alcohol than non-carriers (p=0.038). CONCLUSIONS: Our findings do not support the view that the ΔF508 mutation and 5T allele confer a higher risk of chronic pancreatitis or pancreatic cancer. Nevertheless, our data suggest that interactions between CFTR polymorphism and environmental factors may play a role in the pathogenesis of these diseases. Our study emphasises the need for a multinational study to conclusively establish the role of CFTR variants as genetic susceptibility factors for chronic pancreatitis and pancreatic cancer.